2021
DOI: 10.1002/adfm.202107756
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Organic Solar Cells with Reduced Nonradiative Voltage Loss Enabled by a Highly Emissive Narrow Bandgap Fused Ring Acceptor

Abstract: Increasing the photoluminescence quantum yield (PLQY) of narrow bandgap acceptors is of critical importance to suppress the nonradiative voltage loss (ΔVnr) in organic solar cells (OSCs). Herein, two acceptors, SM16 and SM16‐R, with an identical backbone but different terminal groups (norbornenyl modified 1,1‐dicyanomethylene‐3‐indanone and dimethyl substituted 1,1‐dicyanomethylene‐3‐indanone) are designed and synthesized. Compared with SM16‐R, SM16 displays better solubility, higher PLQY, and more favorable n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…The charge recombination and extraction characteristics have close ties to the charge mobility (μ), which can be estimated via employing the photoinduced charge carrier extraction by linearly increasing the voltage (Photo-CELIV). [55,56] As shown in Figure 3d, the average μ of the optimized ternary OSCs is 1.16 × 10 −4 cm 2 V −1 s −1 , which is larger than 9.98 × 10 −5 cm 2 V −1 s −1 for ternary OSCs with 30 wt% Y6-1O, 9.67 × 10 −5 cm 2 V −1 s −1 for Y7-BO-based binary devices, and 7.49 × 10 −5 cm 2 V −1 s −1 for Y6-1O-based binary devices, which indicates that charge carriers are transported more efficiently in the optimized ternary OSCs. The μ value obtained from the Photo-CELIV measurement is composed of a combination of the electron and hole mobilities, which are dominated by the faster carrier mobility.…”
Section: Resultsmentioning
confidence: 99%
“…The charge recombination and extraction characteristics have close ties to the charge mobility (μ), which can be estimated via employing the photoinduced charge carrier extraction by linearly increasing the voltage (Photo-CELIV). [55,56] As shown in Figure 3d, the average μ of the optimized ternary OSCs is 1.16 × 10 −4 cm 2 V −1 s −1 , which is larger than 9.98 × 10 −5 cm 2 V −1 s −1 for ternary OSCs with 30 wt% Y6-1O, 9.67 × 10 −5 cm 2 V −1 s −1 for Y7-BO-based binary devices, and 7.49 × 10 −5 cm 2 V −1 s −1 for Y6-1O-based binary devices, which indicates that charge carriers are transported more efficiently in the optimized ternary OSCs. The μ value obtained from the Photo-CELIV measurement is composed of a combination of the electron and hole mobilities, which are dominated by the faster carrier mobility.…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43][44] We introduced the three-dimensional shape-persistent norbornyl-modified 1,1-dicyanomethylene-3-indanone (IC) terminal group to the acceptor molecules and found that such a bulky terminal group could markedly enhance the solubility of the acceptor molecules, optimize the morphology of the blend film, and decrease the non-radiative voltage loss. [45][46][47] Furthermore, isomerization is an effective approach for finetuning the photovoltaic properties of organic solar cells. Isomerized materials usually show large differences in their electronic structure, absorption spectra, charge transport, and molecular stacking, which are mainly due to different steric hindrance or intramolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…41–44 We introduced the three-dimensional shape-persistent norbornyl-modified 1,1-dicyanomethylene-3-indanone (IC) terminal group to the acceptor molecules and found that such a bulky terminal group could markedly enhance the solubility of the acceptor molecules, optimize the morphology of the blend film, and decrease the non-radiative voltage loss. 45–47…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] The dramatically improved photovoltaic performance of nonfullerenebased PSCs can be attributed to the merits of NFAs such as the tunable energy levels in a wider range, stronger absorption in the visible and near-infrared (NIR) region in comparison with the fullerene derivatives. [17][18][19] Since the first report of fused-ring electron acceptor (ITIC), [20] diverse structural variants, including side-chain adjustment, [21,22] core modification, [23][24][25] and end-group engineering, [24,26,27] have been widely employed to improve the performance of PSCs as well as to know the relationships between the molecular structure and the photovoltaic properties of NFAs. It has been proven that the end-group engineering not only can significantly impact the optical and electrochemical properties of the resulting acceptor molecule but also can play a vital role in determining the intermolecular π-πpacking arrangement as well as the resulting photovoltaic performance of PSCs.…”
Section: Introductionmentioning
confidence: 99%